From the Book ‘Becoming Critical’: A Short Dialogue for Educator - Suryawahyuni Latief; Wolter Parlindungan Silalahi; Yeni Rachmawati (Indonesia Approach Education, 2020)
This paper performs a narrative analysis of the basic philosophy of education book. The book, “becoming critical” was written by Carr and Kemmis (1986). Authors rise up again this old book due to the whole content is essential for educator, students from undergraduate to doctoral level. In simple, the book narrated three basic educational research methodologies among all chapters: technical-theoretical-positivism, practical-interpretative-hermeneutics, and critical-reflection-emancipatory paradigm. Narrative is the central mechanism for meaning making. It is the multiple representations used to reference and make sense of human experience. Dealing with the pros and cons of those paradigms, this paper gives a brief memory to educator in doing research in education. To sum up, this paper illustrated education, knowledge, and action research.